An experimental study of scaling effects in the perforation resistance of woven CFRP laminates. (1st December 2017) - Xu, Z.W.; Guan, Z.W.; Cantwell, W.J.
Abstract: Scaling effects in the perforation resistance of a carbon fibre-reinforced polymer (CFRP) composite have been investigated under quasi-static and low velocity impact loading conditions. The perforation data have been supplemented with results from additional flexural tests on scaled composite beams, which highlighted a decrease in both strength and failure strain as scale size increases. Strain-rate effects in this composite have been also identified, with the plates absorbing less energy as the loading-rate is increased. Tests on scaled plates have shown that the normalised perforation energy increases rapidly with scale size. An examination of the load-displacement response indicates that the elastic response obeys a simple scaling law, whereas that the damage does not. It was found that fibre damage was more severe in larger composite panels. It is argued that the energy absorbed in fibre fracture does not scale in the expected manner, leading to greater levels of fibre damage in the larger plates.